(untitled) (Political Science Journal, 2025)
Public Private Partnership (PPP) is a concept largely popularized by the multilateral banks and nowadays widely included by the governments of developing nations. PPP covers multiple sectors of infrastructure and services, including education. Also known as e-PPP, the PPP in education has been applied in many countries and is known to have mixed results. Although the e-PPP exists in various forms in Nepal, the Public Private Policy 2015 remotely mentions PPP in education. Although the discussion among the various stakeholders, reports, and reviews highly discusses the role and need of the policies for the management and monitoring of e-PPP in Nepal, there is no clear idea regarding what shall be included in the upcoming e-PPP policy. The authors have used a doctrinal method based on the desk review of the articles, books, policies, and news articles concerned with e-PPP. Furthermore, the authors have focused on the critical examination of e-PPP around the world since it can serve as a lesson for the upcoming e-PPP Policy in Nepal. The paper firstly reviews the various policies directly and indirectly concerned with e-PPP in Nepal, then mentions the current status of e-PPP in Nepal, then discusses the various challenges related to e-PPP in nexus with sustainable development goals and finally it suggests the way forward using the examples of various nations to select a modality that is in tandems with the concerns of all level of governance in Nepal.